2014
DOI: 10.2500/ar.2014.5.0081
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium Chelonae Dacryocystitis after Endoscopic Dacryocystorhinostomy

Abstract: Mycobacterium chelonae is a rapidly growing nontuberculous Mycobacterium and an uncommon cause of aggressive, treatment-resistant ocular and periocular infection. This is the first known case report of a woman who developed unilateral M. chelonae dacryocystitis after undergoing endoscopic sinus surgery and right endoscopic dacryocystorhinostomy (DCR) with Crawford stent placement. We describe our findings and effective methods to manage the infection. Three weeks after undergoing DCR, the patient acutely devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…RGM is widely distributed in nature and isolated from soil, dust, water, and hospital environments (including hospital tap water)[ 4 ]. In particular, M. fortuitum and M. abscesses are relatively resistant to standard disinfectants such as chlorine, alcohols, and formaldehyde and are a common cause of nosocomial infections, including dialysis-associated infections, long term central intravenous catheters, injections, and plastic surgery procedures [ 20 23 ]. Therefore, preventative steps should be taken in medical settings, such as avoiding contact with catheters, medical instruments with tap water, and refraining from washing open wounds with tap water [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…RGM is widely distributed in nature and isolated from soil, dust, water, and hospital environments (including hospital tap water)[ 4 ]. In particular, M. fortuitum and M. abscesses are relatively resistant to standard disinfectants such as chlorine, alcohols, and formaldehyde and are a common cause of nosocomial infections, including dialysis-associated infections, long term central intravenous catheters, injections, and plastic surgery procedures [ 20 23 ]. Therefore, preventative steps should be taken in medical settings, such as avoiding contact with catheters, medical instruments with tap water, and refraining from washing open wounds with tap water [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Ophthalmologic cases of M chelonae have been frequently reported in the literature with ocular tissue being the second most common site of infection following skin and soft tissue. 1,3,4 A 30year retrospective review of biofilm growth on explanted devices demonstrated M chelonae growth on orbital plates, spheres, and predominantly lacrimal stents. 5 Here we present a unique case of M chelonae involving an infected implant for repair of an orbital floor fracture and laceration.…”
mentioning
confidence: 99%